2011
DOI: 10.1007/s12598-011-0187-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behavior of zirconium in molten NaCl-KCl-K2ZrF6 system

Abstract: The electrochemical reduction of Zr 4+ (complex) ions in NaCl-KCl-K 2 ZrF 6 molten salt on Pt electrode was investigated using cyclic voltammetry and square wave voltammetry at 1023 K. Two cathodic reduction peaks related to Zr 4+ /Zr 2+ and Zr 2+ /Zr steps were observed in the cyclic voltammograms. The result was also confirmed by square wave voltammetry. The diffusion coefficient of Zr 4+ (complex) ions at 1023 K in NaCl-KCl-K 2 ZrF 6 melt, measured by cyclic voltammetry, is about 4.22×10 −6 cm 2 /s. The cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The possible reactions might be shown in equations (14) and (15) [29]. The alumina crucible closed to the zirconium metal turns black, as shown in the inset of Fig.…”
Section: Characterization Of the Melt And Byproductsmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible reactions might be shown in equations (14) and (15) [29]. The alumina crucible closed to the zirconium metal turns black, as shown in the inset of Fig.…”
Section: Characterization Of the Melt And Byproductsmentioning
confidence: 99%
“…The chosen of the liquid alloy anode can not only reduce the operating temperature, but also expect to provide a low cost and semi-continuous process for production nuclear grade zirconium. The electrorefining and electrochemical process of Zr has been studied in various molten salt systems, including all-chloride baths such as LiCl-KCl-ZrCl 4 [2,[5][6][7], KCl-ZrCl 4 [8,9], all-fluoride baths such as LiF-NaF-KF-ZrF 4 and K 2 ZrF 6 [10,11], LiF-KF-ZrF 4 [3], LiF-CaF 2 -ZrF 4 [12] and chloridefluoride-mixed baths such as KCl-NaCl-ZrF 4 [13], KCl-NaCl-K 2 ZrF 6 [8,13,14], and LiCl-KCl-K 2 ZrF 6 [15] at temperature ranges of 450 C to 750 C. However, the operating temperature of the all-fluoride baths is 100 C $ 200 C higher, and the corrosion issue is more severe compared to those of all-chloride baths. In consideration of the melting point of liquid alloy anode and a moderate experimental condition, the Zr electrorefining process is proposed in LiCl-KCl-ZrCl 4 molten salt at 500 C in the initial stage of research.…”
Section: Introductionmentioning
confidence: 99%
“…The zirconium electrochemical behaviour, in the form of chloride, has been widely investigated and no consensus on its reduction pathway in chloride melts has been found yet. Authors reported several oxidation states (0, +I, +II and +IV) due to a complex chemistry in chloride and in chloro-fluoride melts [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In the fluoride–chloride system, powdery Zr deposits are known to be produced in LiCl-KCl-LiF-ZrCl 4 [ 12 , 13 , 14 ]. Furthermore, Chen et al [ 15 ] and Wu et al [ 16 ] obtained powdery and dendritic products by using K 2 ZrF 6 as a zirconium source in NaCl-KCl-K 2 ZrF 6 . Relevant studies have shown that powdery products are easy to obtain by electrolytic refining processes in fluoride system and fluoride–chloride system, resulting in a high salt inclusion rate of cathode products and high oxygen content after subsequent water washing treatment.…”
Section: Introductionmentioning
confidence: 99%